GATA3 rs3824662 gene polymorphism as possible risk factor for systemic lupus erythematosus. (November 2018) - Mosaad, Y M; Hammad, A; Elghzaly, A A; Tawhid, Z M E; Hammad, E M; Showma, A; Abdelsalam, R; Elmoughy, A; Fawzy, I M; Anber, N
Background: There is no report about the association between GATA3 rs3824662 polymorphism and systemic lupus erythematosus (SLE). Objective: To investigate the possible role of GATA3 rs3824662 polymorphism as a susceptibility risk factor for either adult SLE (aSLE) or pediatric SLE (pSLE) and to evaluate its role in the development of lupus nephritis (LN) in pSLE. Methods: Typing of GATA3 rs3824662 polymorphism was done using real-time polymerase chain reaction for three groups; 104 pSLE patients, 140 aSLE patients and 436 age- and sex-matched healthy controls. Results: Non-significant differences were found between SLE patients and healthy controls for the allele and genotype frequencies of GATA3 rs3824662 ( p  > 0.05). In pSLE; the AC genotype was associated with LN ( p  = 0.04); the A allele and AC genotype were associated with persistent proteinuria ( p  = 0.036 and 0.01, respectively) and both the A allele and AA genotype were associated with higher chronicity index ( p  = 0.031 and 0.04, respectively). In aSLE; the C allele was associated with cellular cast ( p  = 0.03) and thrombocytopenia ( p  = 0.01). Logistic regression analysis revealed significant association between the AC+AA genotypes and the prediction of LN and renal active disease in pSLE ( p  = 0.04 and 0.01, respectively). Conclusion: GATA3 rs3824662 is not associated with susceptibility to SLE either in adult or in pediatric patients; however, in pSLE patients, the heterozygous AC genotype could be considered a risk factor for LN. At the same time, the AC and AA genotypes could be considered as predictors for LN and active renal disease. However, the small sample size is a limiting factor of the present study when interpreting the positive association.